Comparative Analysis of Gender-Based Differences in NSCLC between Europe and Asia - Giorlando, María Aimé; Escorial, Carmen; Gabay, Carolina; Ortega, Elias; Mari, Ettore; Andreasyan, Armen; Schnetter, Laura; Mendoza, Luis (British Journal of Healthcare and Medical Research, 2023)
Background: The demographic makeup of lung cancer has shifted over the last decades. Females are more likely to be non-smokers, diagnosed at a younger age, earlier stage, have adenocarcinoma and a family history of cancer. Objectives: the primary objective is to analyze the gender-based differences with regards to clinicopathologic features in Europe and Asia. Methods: This study was based on Oncology Dynamics, using a physician questionnaire. In Q1 2022, IQVIA engaged 1,181 physicians from Europe and 1,402 from Asia. The following items were analyzed: gender, age, smoking status, clinical stage, oncogenic driver status, location of metastases, ECOG, and comorbidities. Results: A total of 18217 cases were analyzed; 7006 (38.5%) were females (F) and 11211 (61.5%) males (M). The percentage of Asian female non-smokers was substantially higher compared to males and European population. Females had more adenocarcinoma and less squamous cell carcinoma cases on both continents. Most patients had metastatic disease at diagnosis. However, in Asia there was a higher proportion of localized disease compared to Europe regardless of sex. The frequency of brain metastases in Asian females was significantly higher (20%) than in Asian males (14%) or the European population (F: 16%, M: 10%). EGFR mutation was the most common oncogenic driver in both genders, but its prevalence was higher in Asian females. Conclusion: This research highlights the differences in cancer staging between Asian and European patients and the importance of gender-based differences suggesting that lung cancer may be increasingly considered a distinct disease in females.